Legal Protection Against Trademark Label Substitution: Analysis Based on Law Number 20 Of 2016 Concerning Trademarks and Geographical Indications - Nur Alma Azizah; Nandita Listia Aprilia; Leistiana; Dudung Hidayat; Raden Handiriono (PT FORMOSA CENDEKIA GLOBAL, 2025)
Replacement labels on products that use registered trademarks are a crucial issue in the protection of intellectual property rights, as stipulated in Law No. 20 of 2016 concerning Trademarks and Geographical Indications. The method used is normative juridical research with a qualitative approach, through literature studies and interviews with legal experts and practitioners in the field of intellectual property. The study's results indicate that current regulations do not specifically address the protection of illegally modified brand labels, leaving legal loopholes that permit abuse. Although the Act grants exclusive rights to trademark owners and imposes the threat of sanctions against violators, its implementation remains limited due to the lack of adequate oversight mechanisms and weak law enforcement. In addition, dispute resolution in cases like this tends to be complex because it involves a complaint and requires difficult proof. At the same time, the litigation process is often time-consuming and expensive. Therefore, this study recommends the need for regulatory reform through more specific implementing regulations, such as Government Regulations on the Use of Trademarks by Third Parties, as well as increased public supervision and education on the protection of trademark rights to ensure legal certainty and justice for registered trademark holders.